Proposal for the Implementation of Canvas and SWOT Analysis Tools in a Small Business - Trevisan, Laís Viera; Fialho, Camila Borges; Coronel, Daniel Arruda (Journal of Sustainable Competitive Intelligence, 2018)
Objective: The study aims to implement strategic management tools, specifically Canvas and SWOT analysis, in a small consulting firm to enhance its business model and strategic planning processes. Method: A descriptive, qualitative case study was conducted. Data were collected through literature review, document analysis, semi-structured interviews with the company's owners, and participant observation. The study focused on understanding and improving the company’s internal and external environments. Results: The implementation of the Canvas tool mapped the company’s business model, identifying customer segments, value propositions, key resources, and revenue streams. SWOT analysis further revealed internal strengths, such as a flexible service offering and strong client relationships, and external opportunities, such as market expansion. Weaknesses, like limited marketing investment, and external threats, including economic challenges, were also identified. Conclusion: The use of Canvas and SWOT analysis provided actionable insights, enabling the company to refine its business model and develop future strategies. These tools supported decision-making by offering a clear structure for analyzing and improving the business.